Unravelling the bending stability of flexible quantum-dot light-emitting diodes. (9th February 2022) - Wang, Rujing; Yuan, Qilin; Kang, Zhihui; Wang, Rong; Zhang, Dandan; Ji, Wenyu
Abstract: The bending stability is still the central obstacle to the practical applications of flexible quantum-dot light-emitting diodes (QLED). Here, we examine the influence of every functional layer, including electrodes, charge injection/transport layers, and emission layer, on the photoelectrical properties of the QLEDs during the bending fatigue test. It is demonstrated that the bottom substrate and top metal electrode play a critical role in determining the bending stability of flexible QLEDs. The bending stability of the QLED can be improved obviously by controlling the elastic modulus and surface roughness of the substrate with a poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) modifying layer inserted between PET/ITO/Ag/ITO and ZnO electron-transport layer. The PEDOT:PSS layer not only reduces the surface roughness, but also causes the neutral mechanical plane of the PET/ITO/Ag/ITO multilayer to move towards the surface of the substrate. The twofold effect of this PEDOT:PSS modifying layer improves the bending stability of the device. Moreover, the device efficiency is also enhanced from 17.9 to 20.4 cd A −1 with the insertion of PEDOT:PSS layer.